The impacts of sector growth and monetary policy on income inequality in developing countries. Issue 3 (2nd August 2019) - Siami-Namini, Sima; Hudson, Darren
Abstract : Purpose: The purpose of this paper is to explore the effect of growth in different sectors of the economy of developing countries on income inequality and analyze how inflation, as a proxy for monetary policy, makes a proportionate contribution for setting a binding national target for reducing income inequality. The paper examines the existence of a linear or nonlinear effect of inflation and sectoral economic growth on income inequality using a balanced panel data of 92 developing countries for the period of 1990–2014. Design/methodology/approach: Methods section includes several steps as below: first, the functional form of the model using panel data for investigating the contribution of economic sectors in income inequality; second, to estimate the relationship between income inequality and sector growth: testing the Kuznets hypothesis; third, to estimate the relationship between inflation and income inequality base on general functional form of the model proposed by Amornthum (2004); fourth, a panel Granger causality analysis based on a VECM approach. Findings: The statistically significant finding shows that first agricultural growth and then industrial growth have a dominate impact in reducing income inequality in our sample. But, the service sector growth has positive effects. The results confirm the existence of Kuznets inverted "U" hypothesis for industry growth and Kuznets "U" hypothesis for service sector growth. The findings show that sector growth and inflation affect income inequality in the long-run. Originality/value: This research is an original paper which analyzes the effect of growth in different sectors of the economy of developing countries (agriculture, manufacturing and services sectors) on income inequality and test the Kuznets hypothesis in terms of sector growth and at the same time, examine the existence of a linear/nonlinear effect of inflation and sectoral economic growth on income inequality and test Granger causality relationship between income inequality and sector growth and inflation.